Design of Future UAV-Relay Tactical Data Link for Reliable UAV Control and Situational Awareness - Baek, Hoki; Lim, Jaesung (IEEE Communications Magazine, 2018)
Unmanned aerial vehicles (UAVs) have recently been widely used in the military and commercial domains. UAVs, especially in the military domain, were initially used for gathering intelligence, surveillance, and reconnaissance data, and sending them to a command center. Their use was then expanded to the tactical level to perform military operations with manned platforms. Operating a UAV as a relay node in the air has many advantages, including coverage, recovery from disconnection from a relay, clear communication channel, and easy deployment. Thus, the UAV-Relay tactical network can support more effective military operations. However, reliable UAV control and situational awareness must be guaranteed for the use of tactical UAVs. In other words, all tactical nodes must be able to send their location and status periodically under the dynamic and unexpected situation of a battlefield. However, a jamming attack from the enemy can make UAV control and situational awareness impossible. Thus, we need a robust tactical data link (TDL) to guarantee reliable UAV control and situational awareness under a jamming attack. In this article, we first explain the requirements for reliable UAV control and situational awareness. We then design a future UAV-relay TDL, called link-situational awareness and control (Link-SAC), which satisfies the requirements. We also deal with the spectrum allocation and management of Link-SAC because Link-SAC requires large bandwidth under the scarcity of spectrum resource. Thus, we consider spectrum sharing to allocate an X-Band uplink to Link-SAC. Based on the interference analysis in a prior study, we show that spectrum sharing is possible. We also show how Link-SAC can manage the spectrum. Lastly, we present our concluding remarks.
Keywords: Intelligence , surveillance , and reconnaissances; Interference analysis; Military domains; Situational awareness; Spectrum allocation; Spectrum sharing; Tactical data links; Tactical data links (TDL)